TLR10 overexpression modulates immune response in A549 lung epithelial cells challenged with SARS-CoV-2 S and N proteins - Knez, Špela; Narat, Mojca; Ogorevc, Jernej (Frontiers in Immunology, 2025)
Toll-like receptors (TLRs) play an important role in the recognition of viral particles and activation of the innate immune system, but their role in SARS-CoV-2 infection is still poorly characterized. In the present study, we investigated the role of Toll-like receptor 10 (TLR10) in modulating the immune response during SARS-CoV-2 infection. The results showed that overexpression of TLR10 in A549 lung epithelial cells, immunostimulated with SARS-CoV-2 proteins S and N mainly downregulated proinflammatory cytokines and interferons and affected gene expression in the cocultured THP-1 monocytes. Our results suggest that TLR10 could mediate the extent of SARS-CoV-2 infection by downregulating the release of inflammatory cytokines and chemokines such as CXCL10, IL6, IL8, and IFNβ. Modulation of TLR10 expression could have implications for the treatment of patients with severe COVID-19, in whom excessive inflammation leading to the development of acute respiratory distress syndrome (ARDS) is a key feature. However, further research is needed to fully understand the impact of modulating TLR10 expression on the antiviral response and the overall balance of the immune response during SARS-CoV-2 infection.